2016
DOI: 10.1021/acs.energyfuels.6b00261
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thermal Treatment on Asphaltene Functional Groups

Abstract: The main objective of this study is to provide an in-depth analysis that reveals the impact of thermal treatment on the different functional groups that exist in asphaltene molecules. This contribution is important to further understand the nature of changes that take place in asphaltenes during distillation and thermal cracking processes. A slight increase was observed in the aromatic −CH groups, compared to aliphatic −CH groups, as crude oil is processed to atmospheric and vacuum residues. A slight decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 70 publications
1
37
0
Order By: Relevance
“…However, the band is weak and also appears in the untreated asphaltene. It can be observed from Figure 4b that a higher transmittance band is obtained for higher exposure time in the ranges 675-900 cm −1 corresponding to aromatic structures (C-O), 1365-1725 cm −1 corresponding to aromatic and aliphatic structures (C-H, C-C, and C=O), 1715 cm −1 band corresponding to the ketone group, and 2800-2900 cm −1 corresponding to aldehyde groups (RR'C=O and C-H) [33]. After oxidation at 1 and 5 h similar results are observed, but after 10 h an increase in the transmittance of approximately 10% is obtained.…”
Section: Ftir Analysis Of Solid Asphaltenesmentioning
confidence: 93%
See 2 more Smart Citations
“…However, the band is weak and also appears in the untreated asphaltene. It can be observed from Figure 4b that a higher transmittance band is obtained for higher exposure time in the ranges 675-900 cm −1 corresponding to aromatic structures (C-O), 1365-1725 cm −1 corresponding to aromatic and aliphatic structures (C-H, C-C, and C=O), 1715 cm −1 band corresponding to the ketone group, and 2800-2900 cm −1 corresponding to aldehyde groups (RR'C=O and C-H) [33]. After oxidation at 1 and 5 h similar results are observed, but after 10 h an increase in the transmittance of approximately 10% is obtained.…”
Section: Ftir Analysis Of Solid Asphaltenesmentioning
confidence: 93%
“…Similarly, for fixed concentrations of 100 and 1000 mg/L, the formation of W/O emulsions shows an increase of 7% and 25%, and 37% and 66% for asphaltenes treatment temperatures of 373 and 473 K. These results indicate that as the asphaltenes concentration increased, the suitability of W/O phase formation increases. As the aromaticity increases, the decrease of side alkyl chains and the reduction of the alkyl chains ramification of the asphaltenes molecule can be responsible for the emulsions stabilization [33]. Also, the decreased solvency of treated samples, which decreases as treatment temperature increases, may lead to a higher preference of asphaltenes for being at the model solution-water interface than in bulk [25].…”
Section: Oxidation Temperature Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…FT-IR results also support that no olefinic hydrocarbon is produced during reaction in presence of acid catalysts. AlHumaidan et al [28] recently used FT-IR technique for detailed characterization of asphaltenes. The major IR peaks were found due to the saturated hydrocarbons as it was also observed in this study.…”
Section: Characteristics Of Liquid Productsmentioning
confidence: 99%
“… 4 The FTIR results suggested that thermal treatment mainly affects the paraffinic side chains in the molecular structure of asphaltenes, while changes in the aromatic core appear to be very limited. 4 In a more recent study, AlHumaidan et al 5 used NMR analysis to identify and quantify the structural parameters and the functional groups from which the hypothetical average structure of different asphaltene molecules were derived. The NMR analysis revealed several valuable findings and developed better understanding about the nature of structural changes that asphaltene molecules undergo during the thermal cracking of VRs.…”
Section: Introductionmentioning
confidence: 99%